Characteristics Ultrasonic Waves Velocity and Anatomical Properties of Tapping Pine - Maryam Jamilah; Lina Karlinasari; Sucahyo Sadiyo; Gunawan Santosa (Masyarakat Peneliti Kayu Indonesia, 2015)
Non-destructive testing based on sound wave propagation has been used widely to estimate wood quality of standing trees. The aim of this study was to evaluate the characteristics of the sound wave velocity in relation to pine resin productivity and resin intercellular frequency and diameter. The samples were 72 trees consisted of 36 trees which were tapped by the quarre method and 36 other trees were tapped with addition of stimulants. The speed of sound waves propagation was measured by SylvatestDuo for radial direction and longitudinal. The tapping position was determined refering to the wind direction. The resin productivity was twice for tapping with stimulant comparing to the control. The highest resin productivity was 87.31 g per harvest for tapping with stimulant and the lowest (39.86 g per harvest) for control. Statistically, there was not significant difference in sound speed for tapped position as well as for measurement before and after tapped of both radial and longitudinal testing, as well as for the anatomical properties of both of treatments. A high positive correlation was found between resin productivity and intercellular frequency for both treatments (r>0.80), however, there was not significance correlation between resin productivity and other parameters.Keywords: Pinus merkusii, resin tapping, sound wave propagation